AN AIR TRAFFIC FORECASTING STUDY AND SIMULATION - PHYOE, S M; GUO, R; ZHONG, Z W (MATTER: International Journal of Science and Technology, 2016)
This paper analyzes the forecasting performance for air traffic movement by comparing different models. The relationship between economic variables and the air traffic demand is analyzed by tracing the past several years’ data. The econometric models are emphasized, and a long-term forecast is concentrated in this air traffic forecasting study. The aim is to find the suitable methods and variables to be applicable to the situation similar to Singapore FIR and also to improve the forecasting accuracy. The conflicts and the density of air traffic in Singapore FIR are estimated in this paper by using the results of forecasting.